Analisis Peran Stakeholder dalam Pelaksanaan Urban Farming di RW 01, Kelurahan Manyaran, Kota Semarang - Wilis Sugesti Wibisono; Abdul Malik (Pusat Riset dan Inovasi Nasional, 2025)
Land use in the Semarang City area shows that about 6.41% of the total area is rice field farmland, while the remaining 93.59% is non-rice field agricultural land or non-agricultural land. The development of urban farming in RW O1, Manyaran is present as an innovative solution to overcome the problem of food security on limited land. The purpose of this study is to examine the identification of the roles of the subjects involved and the forms of contribution given, supporting and inhibiting factors in the field, as well as explore strategies to optimize the role of each stakeholder in increasing the success of urban farming programs in the RW 01 area, Manyaran. This study applies a qualitative method with case studies and follows data collection techniques through observation, semi-structured interviews, and documentation. The results show that multi-stakeholder collaboration is crucial. The Chairman of RW plays the role of coordinator and facilitator. PKK RW 01 became the initiator, while the Chairman of RT mobilized residents. The community actively contributed. Support also comes from the private sector (CSR), religious institutions (training), and academics (innovation, donations). Karang Taruna plays a vital role in maintenance and regeneration. Supporting factors include citizen participation and external support. However, the main obstacles are time constraints, lack of technical expertise, limited tools, land constraints (sunlight), and low awareness among some people. Recommended strategies include increased training, intensive socialization, provision of tools, land optimization, and solid community building. Synergy between stakeholders is very important for the sustainability of urban farming and the improvement of community welfare.